Morphological Differentiation of Oligodendrocytes Requires Activation of Fyn Tyrosine Kinase - Osterhout, Donna J. (The Rockefeller University Press, 1999)
In the central nervous system, myelination of axons occurs when oligodendrocyte progenitors undergo terminal differentiation and initiate process formation and axonal ensheathment. Although it is hypothesized that neuron-oligodendrocyte contact initiates this process, the molecular signals are not known. Here we find that Fyn tyrosine kinase activity is upregulated very early during oligodendrocyte progenitor cell differentiation. Concomitant with this increase is the appearance of several tyrosine phosphorylated proteins present only in differentiated cells. The increased tyrosine kinase activity is specific to Fyn, as other Src family members are not active in oligodendrocytes. To investigate the function of Fyn activation on differentiation, we used Src family tyrosine kinase inhibitors, PP1 and PP2, in cultures of differentiating oligodendrocyte progenitors. Treatment of progenitors with these compounds prevented activation of Fyn and reduced process extension and myelin membrane formation. This inhibition was reversible and not observed with related inactive analogues. A similar effect was observed when a dominant negative Fyn was introduced in progenitor cells. These findings strongly suggest that activation of Fyn is an essential signaling component for the morphological differentiation of oligodendrocytes.